Status Quo Bias in Ballot Wording. Issue 2 (10th November 2017) - Barber, Michael; Gordon, David; Hill, Ryan; Price, Joseph
Abstract: We examine the role of status quo bias in the ballot wording of social issues that affect the rights of minority groups. We test the salience of this framing bias by conducting an experiment that randomly assigns different ballot wordings for five policies across survey respondents. We find that status quo bias changes the percent of individuals who vote for the ballot measure by 5–8 percentage points with the least informed individuals being the most affected by status quo bias.